USM AND YRU STRENGTHENING ASEAN RELATIONS - MPRC, Pusat Media & Perhubungan Awam (USM, 2016)
USM, PENANG, 16 March 2016 – Universiti Sains Malaysia (USM) continues to strengthen relations with universities in the ASEAN region.